Integration of metallacycles and polyoxometalate macrocycles. Issue 5 (13th January 2021) - Zhu, Zeng-Kui; Lin, Ya-Yun; Li, Xin-Xiong; Zhao, Dan; Zheng, Shou-Tian
Abstract : A series of polyoxometalate–metallacycle composite macrocycles with interesting bi/tri-layer cyclic structures have been synthesized, which show a remarkable integration of metallacycles and polyoxometalate macrocycles at molecular level. Abstract : We demonstrate a remarkable integration of metallacycles and polyoxometalate (POM) macrocycles at the molecular level, forming a series of unprecedented organic–inorganic hybrid POM–metallacycle composite macrocycles with interesting bi-layer and tri-layer cyclic structures, as well various compositions, nuclearities, geometries, and sizes. These molecular composite macrocycles show a fusion of metallacycle and POM chemistry, which opens new perspectives for developing brand-new ring-shaped composite materials.